Proposal for an Analytical Model for Sports Migration - Rojo, Jeferson Roberto; Starepravo, Fernando Augusto (Journal of Sports Research, 2021)
The purpose of this study was to present a proposal for an analytical model for sports migration studies is presented. The model was developed by sports Researchers located in Brazil and seeks to broaden the perspective of the migratory phenomenon in the social field of sports. The model is based on the understanding that the migration process in the sports sector is influenced and shaped by a set of four dimensions, namely, political, cultural, economic, and personal. It is believed that the proposal is legitimized by the needs identified from the literature, adding different perspectives to analyse the phenomenon, thus reducing any dichotomies and limitations of view. In addition to being a point of view that starts from the perspective of the global south.